Raymond Moore's uncertain places. (4th May 2022) - Scanlan, John
Abstract : This article examines the work of late British photographer Raymond Moore (1920–1987) and the ways in which his images of landscapes and objects allow us to understand his work as being driven towards encounters with what I term uncertain places, which is to say places in transition or between states of being that also point the observer of these images to that which lies beyond even photographically-aided perception. This idea is further examined in terms of Moore's acceptance that as a photographer he was but one element in a human-technological process, something that separated his work from the predominant trends in documentary realism that dominated public perceptions of photography during the late period of his career. The uncertain places of Moore's photography, it is argued, matched his temperamental attitude towards his craft and his willingness to allow landscapes and objects, in a sense, to emerge or reveal themselves rather than objectifying or representing them in any conventional sense.